Analysis and evaluation of brush-DC equivalent controlled multiphase cage induction machine drive - Gule, Nkosinathi (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Electrical and Electronic Engineering))--University of Stellenbosch, 2011.